Fundamentals of Nuclear Pharmacy - Saha, Gopal B. (Springer International Publishing, 2018)
Currently an estimated 17 million nuclear medicine procedures are performed each year in the US and constantly evolving, as new radiopharmaceuticals and imaging techniques are introduced for better diagnosis and treatment of human diseases. In keeping up with new developments, the Seventh Edition of Fundamentals of Nuclear Pharmacy chronicles the advancements in radiopharmaceuticals and their use in clinical applications. It discusses basic concepts such as the atom, radioactive decay, instrumentation and production of radionuclides, and explores the design, labeling, characteristics and quality control of radiopharmaceuticals. Radiation regulations and diagnostic and therapeutic applications of radiopharmaceuticals are detailed. Thoroughly updated, the Seventh Edition includes new topics such as alternative productions of 99Mo; production of 64Cu, 86Y, 89Zr, 177Lu, 223Ra; synthesis and clinical uses of new radiopharmaceuticals such as DaTscan, Xofigo, Amyvid, Neuraceq, Vizamyl, Axumin and 68Ga-DOTATATE; dosimetry of new radiopharmaceuticals; theranostic agents and translational medicine. It features numerous examples, diagrams, and images to further clarify the information and offers end- of-chapter questions to help readers assess their comprehension of the material. Recognized as a classic text on nuclear chemistry and pharmacy and acclaimed for its concise and easy-to-understand presentation, Fundamentals of Nuclear Pharmacy is an authoritative resource for nuclear medicine physicians, residents, students, and technologists. .